2000
DOI: 10.1038/sj.leu.2401898
|View full text |Cite
|
Sign up to set email alerts
|

Colony-forming unit-megakaryocyte (CFU-meg) numbers and serum thrombopoietin concentrations in thrombocytopenic disorders: an inverse correlation in myelodysplastic syndromes

Abstract: We studied both serum-free colony-forming unit-megakaryocyte (CFU-meg) numbers and serum thrombopoietin (TPO) levels in 14 patients with aplastic anemia (AA), 37 patients with myelodysplastic syndromes (MDS) and 23 patients with idiopathic thrombocytopenic purpura (ITP) to assess thrombopoiesis in these thrombocytopenic disorders. The mean CFU-meg numbers were lower in AA and MDS patients (10.7 ؎ 11.4 and 42.3 ؎ 58.5/10 5 BMLD cells) than in healthy controls (103.1 ؎ 57.3/10 5 BMLD cells) (P Ͻ 0.0001 and P = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previous studies on the number of CFUMks in chronic ITP showed conflicting results, depending on the assay that was used, the stage (acute or chronic) of the disease, and the refractoriness of the ITP to therapy. Several authors 27,28 found a significant increase in number of CFU-Mks in chronic ITP patients. Others 29,30 reported a reduced number of CFU-Mks in chronic ITP.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies on the number of CFUMks in chronic ITP showed conflicting results, depending on the assay that was used, the stage (acute or chronic) of the disease, and the refractoriness of the ITP to therapy. Several authors 27,28 found a significant increase in number of CFU-Mks in chronic ITP patients. Others 29,30 reported a reduced number of CFU-Mks in chronic ITP.…”
Section: Discussionmentioning
confidence: 95%
“…Serum concentrations of endogenous TPO (eTPO) reflect its constitutive production by the liver and its clearance through binding and internalization by Mpl, the TPO receptor found on the surfaces of platelets and megakaryocytes [10,11]. Several studies have reported increased amounts of eTPO in patients with thrombocytopenia secondary to aplastic anemia, amegakaryocytic thrombocytopenia, and myeloablative chemotherapy [12][13][14][15][16][17][18][19]. In contrast, eTPO levels are not increased in patients with ITP, despite the markedly reduced number of circulating platelets [14][15][16]20].…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In keeping with a stem/myeloid progenitor defect, there is reduced in vitro long-term culture-initiating cell activity 27 and decreased numbers of erythroid, granulocyte, and megakaryocyte colonies. 28,29 Given the heterogeneity of low-risk MDS, it is likely that the mode of pathogenesis will differ between individual patients. However, the functional consequence of bone marrow proliferation and dysplasia could alight on a final common pathway, which may allow detection of common changes among apparently disparate patients.…”
Section: Introductionmentioning
confidence: 99%